Pengaruh Pemberian Monosodium Glutamat Dosis Tinggi terhadap Kadar Serum Urea-Kreatinin pada Tikus Wistar - Nisa, Hayatin; Syamsun, Arfi; Lestarini, Ima Arum (Jurnal Kedokteran, 2013)
Background: Many cases of Monosodium Glutamate (MSG) consumption were found. Many food producers, even restaurant and household add MSG on the food produced. Safety use of MSG is still being debated. Some have claimed that the use of MSG is safe within certain limits, but the results of several studies in animals found that MSG affects the body's organs. MSG that accumulates in the body will interfere, especially the urinary system (kidneys), liver, brain, hematopoietic system, cardiovascular, central nervous system, and reproductive system. The aim of this study was to detect the effect of MSG in highrise dosage towards the level of serum urea-creatinine on Wistar Rats (Rattus novergicus). Methods: The research used a simple experimental design which iscalled the post-test only control group design. This research wasconducted on five sample groups: one group as a control, and fourothers as the treatment. The control group was not given MSG, butaquadest, while the treatment groups were given MSG solution orallyin gradable dose. MSG solution dose that was given in treatment group1 (P1) were 400 mg/100gBB, while the MSG dose for treatment 2 group(P2) were 800 mg/100gBB, treatment 3 group (P3) were 1200 mg/100gBB,and treatment 4 (P4) were 1600 mg/100gBB that were divided into 2doses. After 14 days, mice anesthetized with diethyl ether, thendecapitation and its blood was taken by intracardiac to determineserum urea-creatinine level on Wistar Rats. Result: There was significant effect of administration MSG on serum urea-creatinine levels on Wistar Rats (p <0.05). The result of this study also showed that higher doses of MSG were given, higher meanlevels of serum urea produced, while serum creatinine levels remainedrelatively constant for each group. Conclusion: There was significant effect of giving MSG on serumurea-creatinine levels on Wistar Rats statistically (p <0.05). Keywords: MSG, 14 days, Highrise Dosage, Urea, Creatinine.